2014
DOI: 10.1021/jp501996f
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Mode Excitation in a Partially Illuminated Silver Rod

Abstract: Using electrodynamics theory, we numerically demonstrated that when the incident light polarization direction is parallel to a silver rod axis, the modes that are forbidden in a fully illuminated silver rod can be excited when the rod is partially illuminated. The modes are excited due to the symmetry breaking of the rod when it is partially illuminated. They are characterized by the even number of nodes in the excited surface plasmons and quadrupole pattern of the scattered light in the space. These modes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In previous theoretical work on Au bipyramids, 35 reporting on plane wave versus local (yet external) plasmon excitation, results were evaluated in frequency domain such that a plasmonic horizon due to the limited plasmon lifetime remained elusive. This holds as well for the work by Zhou et al 36 who simulated local excitation of rods. Nevertheless they found that breaking of the rod symmetry influences the emission spectrum.…”
Section: Nano Letterssupporting
confidence: 82%
“…In previous theoretical work on Au bipyramids, 35 reporting on plane wave versus local (yet external) plasmon excitation, results were evaluated in frequency domain such that a plasmonic horizon due to the limited plasmon lifetime remained elusive. This holds as well for the work by Zhou et al 36 who simulated local excitation of rods. Nevertheless they found that breaking of the rod symmetry influences the emission spectrum.…”
Section: Nano Letterssupporting
confidence: 82%
“…Different from the situations when the rod is oriented along the Y axis, the peak intensity at the wavelength of 580 nm is the highest when p 2 = 10 nm, then the intensity gradually drops with increasing p 2 and the resonance peak totally vanishes when p 2 is increased to 50 nm, where the molecule is located at the center of the rod. The change of the resonance peak is related to the symmetry of the system which had been discussed previously . We calculated the Raman enhancement factors of the molecule and the enhanced local electric field, | E | 2 , at the position of the molecules when the rod alone is illuminated by a plane wave at the wavelengths of 400 and 580 nm.…”
Section: Resultsmentioning
confidence: 97%
“…The relative change of the peak intensity is very similar to the scattering spectra variation in a partially illuminated silver rectangular prism where details had been discussed in the previous paper. 47 The enhancement factor of the Raman scattering is obtained by dividing the scattering cross section of the molecular dipole when the nanoparticle is included over that of an isolated molecular dipole at a given wavelength as shown in Figure 2b. We also calculated the enhanced local electric field |E| 2 of the silver nanoparticle at the corresponding positions of the molecule at the wavelengths of 400 and 580 nm when the rod alone is illuminated by a plane wave.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations